Using Instructional Coaching to Support Student Teacher-Cooperating Teacher Relationships. (2nd July 2020) - Richardson, Greer; Yost, Deborah; Conway, Thomas; Magagnosc, Allison; Mellor, Alana
ABSTRACT: This study examines the perceptions of relationship quality and satisfaction held by student teachers and their cooperating teachers within the context of an instructional coaching framework-focused student teaching experience. Cooperating teachers operated as instructional coaches who then provided turn-around training for other cooperating teachers. Independent sample t-tests compared perceptions of the student teaching experience for student teachers and their cooperating teachers with two levels of training as measured by the Coaching Relationship Questionnaire. The instructional coach-trained cooperating teacher group showed advanced psychosocial mentoring, dyad satisfaction and dyad similarity as compared to the turn-around-trained cooperating teacher. However, regardless of training level, positive perceptions of the student teaching experience were reported. Additionally, elements of the instructional coaching framework that were found to be beneficial to cooperating teachers serving as coaches for student teachers were examined in light of the outcomes of the questionnaire. Based on findings, a model of training for cooperating teachers is considered.